China’s readiness for transitioning to a low-carbon economy: mitigant and catalyst factors for a geopolitical conflict - Chen, Yan; Lyu, Jiayi; Ortiz, Jaime; Song, Wenbin (Frontiers in Environmental Science, 2025)
The transition from a carbon-intensive economy to a carbon-neutral one has become a critical global objective to address climate change. This study examines the relationship between Low-Carbon Economic Development (LCED) and Geopolitical Risk (GPR) in China by focusing on the challenges and opportunities they present. We use a qualitative analysis to identify that rising GPR, exacerbated by market instability, resource allocation conflicts, and trade disputes, significantly hinders LCED progress. However, these geopolitical tensions also act as a catalyst for accelerating the development of renewable energy, reducing reliance on traditional energy sources, and fostering low-carbon technologies. Furthermore, LCED can ameliorate GPR by decreasing dependence on energy imports, promoting international cooperation, and encouraging scientific innovation. These findings suggest actionable policy recommendations to support the global transition to a low-carbon economy. This research underscores the potential LCED has as a fundamental tool for resolving geopolitical tensions and uniting global efforts to combat climate change.